HOW P. TILLICH ANSWERS THE FUNDAMENTAL QUESTION OF ONTOLOGY - Tomas Kačerauskas (Problemos)
The fundamental question of ontology emerges as gapi between a subject and an object in "Systematc Theology" of P. Tillich.Tillich opposes to both the tradition of empiricism and the tradition of rationalism. Following epistemic monism of the phenomenology Tillich , as a theologian, is looking for irrational ground of unity. This one is for him not only epistemic but also ontological. Therefore Tillich is close to philosophy of existence and ontology of Heidegger. The holiness, ecstasy, miracle and love are analysed in the context of language philosophy of latest Heidegger here. Their function is to displace (not to transcend). These acts of the divine revelation become like a symbol. The human being and the divine being in the symbol intersect there. This unity fills the foundation gap of ontology.